OWE-030 A dose ranging study of trans-spinal magnetic stimulation for the treatment of faecal incontinence. (8th June 2018) - Hamdy, Shaheen; Xiang, Xuelian; Sharma, Amol; Patcharatrakul, Tanisa; Parr, Rachael; Hall, Patricia; Abukardugha, Ali; Rao, Satish
Abstract : Introduction: Current treatments for faecal incontinence (FI) are only modestly effective. FI is characterised by significant anorectal neuropathy, yet treatments for neuropathic FI are limited. In a randomised dose ranging trial, we investigated the plausibility and optimal frequency of a novel neuromodulation therapy by administering repetitive translumbar (rTLMS) and transsacral magnetic stimulation (rTSMS) in patients with FI Methods: FI patients (≥1 episode/week) were randomised to receive weekly rTLMS and rTSMS treatments with either 1 Hz, 5 Hz, or 15 Hz, over six weeks. Two trains of 300 stimulations each were given at 4 sites (Total ≥2400 pulses), by applying transcutaneous magnetic stimulation via a focal coil to the lumbar and sacral regions. Daily FI episodes and bowel symptoms were assessed with prospective stool diaries and compared before and after treatment. FI severity index (FISI) and subject's global assessment (SGA) were also compared. Patients with ≥50% decrease in weekly FI episodes were considered responders. Results: Twenty-six FI patients, F/M≥18/8 participated; 9 were randomised to 1 Hz, 8 to 5 Hz and 9 to 15 Hz respectively. Results summarised in Table 1. The weekly FI episodes decreased significantly in the 1 Hz (p≥0.004) and 15 Hz group (p≥0.023), but not in 5 Hz group (p≥0.281) when compared to baseline, but there was no difference between groups (p=0.170). There was a significant difference between responder rates (p=0.024) with the 1 Hz group showing a significantly higher responder rate (88.9%) than the 5 Hz group (25%), but not between other groups. After treatment, the FISI score increased by 34.6%±18.4% in 1 Hz group, 12.0%±4.9% in 5 Hz group, and 17.6%±16.1% in 15 Hz group, but there was no difference between groups (p≥0.652). Complete or considerable improvement in FI symptoms was reported by 66.7% in 1 Hz group, 37.5% in 5 Hz group and 44.4% in 15 Hz group (p≥0.480). One patient had numbness/tingling in the right arm in 5 Hz group. Conclusions: In this interim analysis, repetitive translumbar and transsacral magnetic stimulation appears safe, and at 1 Hz frequency showed significant superiority when compared to higher frequencies for the treatment of FI. This non-invasive neuromodulation modality offers promise as a novel treatment approach for FI.